Analysis of technological innovation strategy for small and medium companies of the aeronautical sector - Marcela Barbosa de Moraes; Francisco Cristovão L. Melo; Edson A. A. Querido Oliveira; Arnoldo Souza Cabral (Journal of Aerospace Technology and Management, 2010)
The inherent risk in high-tech activity requires the construction of technological strategies that serve global strategy of the company. The present study aimed to characterize the technological position of small and medium technology-based companies of the aeronautical sector located in the Vale do Paraíba, and to examine whether these companies have a technological strategy formalized and disseminated. The adopted methodology was a descriptive exploratory research, carried out through in-depth individual interviews conducted with the small e medium company’s owners of the cities of Caçapava, São José dos Campos and Taubaté, Brazil. The authors concluded that it is necessary that companies, especially small and medium-sized, adopt a technological innovation strategy integrated with the company’s overall strategy. This will help keeping them competitive within their specificities, and not only in the domestic market, but also in international markets.